Gender equality: moving into a new South African era - Golden, Tanya (Institute of Development and Labour Law, 2026)
{Biological differences are believed to be responsible for the differences in i both behaviour of men and women and the roles they play in society. These differences have sometimes been seen as the basis for inequalities between them and these differences have mainly been responsible for developing ½ theories of gender inequalities. 1 Equal opportunity legislation has given • women recognition as equal in employment opportunities. This legislation has given women the opportunity to test gender equality in present day South Africa. It is this quest for complete gender equality and equal opportunity legislation that I intend to analyse to see if it adequately satisfies equality in the workplace. As a framework for this analysis, it is important to consider the basic concepts of equality and fairness to illustrate what non-discriminatory legislation is and it's true effect in an employment situation. My analysis will focus largely on the new Labour Relations Act of 1995, South Africa's interim constitution, relevant International Labour Organisation conventions and Recommendations, other applicable foreign surveys and lastly employment equity measures.